1962
DOI: 10.1002/jctb.5010120410
|View full text |Cite
|
Sign up to set email alerts
|

The roasting of precipitated copper sulphide

Abstract: The roasting of precipitated copper sulphide in a current of air has been investigated by thermogravimetric analysis in the temperature range 150–800° under isothermal conditions. Chemical analysis of the products was carried out at intervals in each case to determine the distribution of copper between the sulphide, sulphate and oxide forms, and X‐ray diffraction patterns were used to identify the state of the solid phases. During roasting, cupric sulphide is converted to the cuprous state, formation of sulpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1965
1965
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Further investigation by Razouk et al [22,38] confirmed by thermogravimetric analysis simultaneous formation of CuSO 4 , but also suggested that mass loss can be also assigned to dissociation process of CuS followed by the sulfur oxidation:…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Further investigation by Razouk et al [22,38] confirmed by thermogravimetric analysis simultaneous formation of CuSO 4 , but also suggested that mass loss can be also assigned to dissociation process of CuS followed by the sulfur oxidation:…”
Section: Resultsmentioning
confidence: 94%
“…Then, at approximately 450°C, sample mass decreases until the temperature reaches 750°C. Copper sulfate hydroxides and their hydrates formed during annealing are converted to copper oxide sulfate and copper oxides [22,24,25,37,38]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation